2022
DOI: 10.1002/jwmg.22227
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing perennial cover as a driver of duck nest survival in the Prairie Pothole Region

Abstract: Conservation plans designed to sustain North American duck populations prominently feature a key hypothesis stating that the amount of the landscape in perennial cover surrounding upland duck nests positively influences nest survival rates. Recent conflicting research testing this hypothesis creates ambiguity regarding which management actions to pursue and where to prioritize conservation delivery. We compared existing models and new formulations of existing models explaining spatiotemporal variation in nest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…States PPR, which also demonstrated that the positive response of nest survival to perennial cover is reduced, and may decline, when perennial cover dominates a landscape (Pearse et al 2022). While the mechanism is unclear, this may reflect a shift in predation rate as predator community and habitat composition change from grasslands in the south to aspen parkland in the north , Sargeant et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…States PPR, which also demonstrated that the positive response of nest survival to perennial cover is reduced, and may decline, when perennial cover dominates a landscape (Pearse et al 2022). While the mechanism is unclear, this may reflect a shift in predation rate as predator community and habitat composition change from grasslands in the south to aspen parkland in the north , Sargeant et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Sovada et al (2000) observed a positive relationship between grassland patch size and duck nest success, primarily due to increased predator efficiencies and marginal nest success in small, isolated patches. Other researchers also reported increased nest survival with more grassland (Duebbert and Kantrud 1974, Greenwood et al 1995, Stephens et al 2005) though recently that relationship has been challenged by Pearse et al (2022).…”
Section: Discussionmentioning
confidence: 98%
“…We sought to characterize metrics for grassland and wetland availability surrounding surveyed wetlands to evaluate relationships between landscape composition and wetland occupancy by broods. Grasslands have been considered important determinants of duck nesting success in many studies (Greenwood et al 1995, Reynolds et al 2006, Pearse et al 2022). Bloom (2010) demonstrated female mallards selected areas with greater wetland densities to raise a brood, presumably because of reduced duckling survival with increased overland travel in areas with few wetlands (Rotella and Ratti 1992 b , Ball et al 1995), increased competition from conspecifics in low wetland density areas (Krapu et al 1997), or fewer available inundated wetlands as dry summer conditions progress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of prairie buffers (surrounding wetlands), agricultural runoff into wetlands is associated with greater rates of sedimentation, increased nutrient loads, and pesticide impacts [50,[75][76][77], which in turn can alter the chemical and biotic composition of affected wetlands. The loss of surrounding grasslands also becomes a loss of habitat and inter-wetland connectivity for species that require grasslands in addition to ponded wetlands to complete their lifecycle, e.g., waterfowl, amphibians [78][79][80][81]. The cumulative effects of wetland loss and the conversion of prairie to cropland in the PPR have simplified the spatial distribution of wetland basins and the upland landscapes in which they are embedded, and reduced ponded-water variability in remaining wetlands.…”
Section: Mechanisms For Ecosystem Homogenization In the Pprmentioning
confidence: 99%